An Overview of Depression Levels Among the Elderly at the Technical Implementation Unit (UPT) of Social Services for the Elderly, Social Agency, Binjai, North Sumatra Province - Deskrisman Stefan Mendrofa (BEST Journal (Biology Education, Sains and Technology), 2026)
Aging is a natural biological process that brings various biological, psychological, and social transformations. One psychological disturbance that frequently emerges among institutionalized older adults is depression, resulting from separation from family, declining health, and feelings of loneliness. Objective: This study aims to describe the levels of depression among older adults residing in the Technical Implementation Unit (UPT) of Social Services for the Elderly, Social Agency, Binjai, North Sumatra Province. Methods: This descriptive quantitative study involved 62 elderly residents selected using simple random sampling techniques. Data collection was performed using the standard Geriatric Depression Scale (GDS-15) questionnaire. Data were analyzed using descriptive statistics to determine percentages and frequency distributions. Results: The findings demonstrated that out of 62 respondents, 18 older adults (29.0%) experienced mild depression, 24 older adults (38.7%) fell into the moderate depression category, 6 older adults (9.7%) experienced severe depression, while the remaining 14 respondents (22.6%) showed no depressive symptoms. Moderate depression was predominant, particularly among elderly individuals aged over 70 years, those with lower educational backgrounds, and those who were widowed or separated. Conclusion: The prevalence of depression among institutionalized elderly individuals remains significantly high. It is recommended that institutional authorities implement standard adaptive psychological therapies and structural recreation to mitigate and optimize the psychological well-being of the elderly.